1978
DOI: 10.1128/iai.19.1.79-86.1978
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of endotoxemic effects in C3H/HeJ mice with glucocorticoid antagonizing factor and partial characterization of the factor

Abstract: C3H/HeJ mice were used to study the origin and nature of endotoxin-induced glucocorticoid antagonizing factor (GAF). In conventional mice GAF is believed to be responsible for a variety of effects that occur as a result of an injection of endotoxin, including the inhibition of hormonal induction of hepatic phosphoenolpyruvate carboxykinase and of glyconeogenesis. Responses in such animals are seen whether the endotoxin is extracted with phenol-water or with trichloroacetic acid. C3H/HeJ mice do not respond (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
(17 reference statements)
0
19
0
Order By: Relevance
“…Endotoxin-resistant C3H/HeJ mice exhibited a deficiency of IL-1 (371, TNF (38), CSF (39,40) and GAF (41) release together with no febrile response (42) to LPS as compared with endotoxin-sensitive CeH/HeN animals. However, the C3H/HeJ mice did respond appropriately to IL-1 with hypoferremia and neutrophilia (42) and to GAF with antagonism to glucocorticoids (41). These findings indicate that LPS-resistant mice have a defect in cytokine production in response to LPS but not in cytokine activity.…”
Section: Resultsmentioning
confidence: 98%
“…Endotoxin-resistant C3H/HeJ mice exhibited a deficiency of IL-1 (371, TNF (38), CSF (39,40) and GAF (41) release together with no febrile response (42) to LPS as compared with endotoxin-sensitive CeH/HeN animals. However, the C3H/HeJ mice did respond appropriately to IL-1 with hypoferremia and neutrophilia (42) and to GAF with antagonism to glucocorticoids (41). These findings indicate that LPS-resistant mice have a defect in cytokine production in response to LPS but not in cytokine activity.…”
Section: Resultsmentioning
confidence: 98%
“…Berry and his colleagues (13,19,20) demonstrated that endotoxemic mice produce a humoral mediator (GAF) in serum from macrophage and that zymosantreated mice showed higher GAF titers in serum than normal mice after endotoxin challenge. The GAF preparation which they used was partially purified by toxin enhances its release from RES macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…McCallumn and Berry (18) observed that hepatic gluconeogenesis shows severely impaired glycogen synthesis in endotoxemic animals, and also reported that endotoxin prevents the induction of phosphoenolpyruvate carboxykinase (PEPCK) activity after cortisone administration (5). Berry and his colleagues demonstrated that endotoxin-poisoned mice produced a glucocorticoid antagonizing factor (GAF) which inhibits the gluconeogenesis stimulated by steroid administration and that zymosan-treated mice showed higher GAF titers in serum than normal mice 510 S. SAKAGUCHI AND K. YOKOTA after endotoxin challenge (14,19,20). It was found that this factor is produced within 2 hr of an endotoxin injection and exerts at least some of its effects on hepatocytes during the first few hours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this was first demonstrated (in Joe Berry's laboratory in Austin, Tex.) by showing that C3H/HeJ mice, while refractory to the ability of LPS to block gluconeogenesis, were susceptible to the transfer of this activity via peritoneal exudate cell supernatants from wild-type mice exposed to LPS (285,286). A few years later, the idea of the effects of LPS in mammals being mediated by soluble factors generated by host cells had become a widely accepted principle (273).…”
Section: Cytokine Theory Of Disease the Pre-rtnf Eramentioning
confidence: 99%